Foresight in Education ? How Future Determines the Present? - Błajet, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2011)
One of the main challenges of education, if not the most important, is the preparation of a human being to function in the future. And here comes a basic question of what the future is. The task of a qualitative description of what will take place in one, five or twenty years' time seems almost impossible. However, for several dozen years, such attempts have been undertaken. They are called foresight. They are not purely theoretical ? getting to know the future is to be translated into concrete activities in the present time. Therefore we encounter here a practical application of a phenomenon known from quantum physics ? a reversal of the time arrow. We do this and that, but not because the tradition and our experiences tell us to do so, but because our actions are determined by the light cone of possible future events. Therefore Foresight seems to be a precious tool that serves man?s development.